Survey of Knowledge on Injury Treatment in Students of State High School of Sports East Java - MOCHAMAD GUFRON; DONY ANDRIJIANTO (Universitas Pendidikan Indonesia (UPI), 2022)
Introduction: there are still many injuries experienced by students in education. As is the case at the Sports State High School, there are various kinds of fields, some of which are made of cement, grass, sand, etc.; each area has different injuries from one student to another; therefore, students must know more about the impact and risks from the field so that students can be more anxious when carrying out the training program. Purpose: This study aimed to determine the knowledge of the handling of injuries in SMA Negeri Sports East Java students. The type of research in this article uses descriptive quantitative. Methods: The method used by the researcher is using the survey method, which is a method used to examine current events or phenomena that are currently happening. The instrument used is a questionnaire in the form of multiple-choice questions, as many as 31, adopted from previous researchers. The population used was 78 students, while the selected sample was the entire population with a total sampling type sample because the researcher took the sample as a whole, so he used this type of sample. Â Results: From the results of the data analysis, the discussion, and research results, it can be concluded that the knowledge level of students in classes XI MIPA 1, XI MIPA 2, XI IPS 1, and XI IPS 2 at SMA Negeri Sports East Java is in the